Investigation of Japan's value chain through R&D and innovation under demographic change: Implications for digitalization in the post-COVID-19 era - Michael C. Huang; Masahiro Kuroda (Asian Development Bank Institute (ADBI), 2021)
The global COVID-19 pandemic has substantially changed the structure of the economy from the pattern of a supply chain system driven by massive production and consumption to effectual demand through information and communication technology (ICT). Moreover, the transition of work style based on telecommunication stimulates a radical movement toward the Internet of Things (IoT) and artificial intelligence (AI), contributing to the creation of an environment that fosters a super-smart society. To accommodate this trend, advocacy for the creation of Japan's Digitalization Agency in 2020 was a symbolic turning point. This paper aims to investigate the change in Japan's value chain in the circumstances of the demographic transition by using the SciREX Policy Intelligence Assistance System-Economic Simulator (SPIAS-e) for a 50-year projection. The simulation results showed that public investment could increase the productivity for intra-firm ICT and intra-firm R&D activity, while the price index of main product sectors would drop significantly. The demonstration of disguised employment also provides implications for deregulation of working hours and the increasing demand for R&D human resources. An active structural reform for promoting innovation is desirable in the conditions of drastic demographic changes and the post-COVID-19 era.
Keywords: C68; O14; J11; 330; CGE model; value chain; STI policy; SPIAS-e; Japan; R&D; innovation